1995
DOI: 10.1111/j.1600-0528.1995.tb00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Social and behavioural indicators of caries experience in 5‐year‐old children

Abstract: The aim of this study was to investigate the relative influence of socio‐economic status and behaviour on dental health of 5‐yr‐old children. Dental data from a representative sample of 5‐yr‐old children from Lothian, Scotland, were analysed in combination with reported behavioural data collected by standardised telephone interviews of the mothers. Dental data was established for 520 children. A total of 324 mothers of these children were interviewed giving a response rate in relation to the original sample fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
30
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 19 publications
7
30
0
3
Order By: Relevance
“…It could also be detected that the frequency of xerostomic children was null in the whole sampling. The results on buffer capacity showed that 47.7% (112) of the sample presented normal values of pH (between 5 and 7), and 37.4% (88) ues of CFU/ml > 400; 15.9% (38) showed values < 100 and 11.3% (27), values from 100 to 400. In 52.7% (126) of the samples such microorganisms were not detected.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…It could also be detected that the frequency of xerostomic children was null in the whole sampling. The results on buffer capacity showed that 47.7% (112) of the sample presented normal values of pH (between 5 and 7), and 37.4% (88) ues of CFU/ml > 400; 15.9% (38) showed values < 100 and 11.3% (27), values from 100 to 400. In 52.7% (126) of the samples such microorganisms were not detected.…”
Section: Resultsmentioning
confidence: 94%
“…In the Third World countries and in some developed countries it has been verified that the less favored socioeconomic classes are the most affected by dental caries 32 -the highest prevalence of caries is observed in those who possess the smallest purchasing power. In Saudi Arabia, the prevalence of caries was also evaluated in preschool children from different socioeconomic categories: the highest values were verified in children who belonged to the lowest socioeconomic categories, showing that dental caries in children seem to be associated with the social stratum, when it is particularly characterized by the level of the parents' occupation 27 . The association between dental caries and several factors such as dietary habit, utilization of fluorine, socioeconomic and cultural factors, as well as the access to dental care has been clearly demonstrated in several investigations 8,16 .…”
mentioning
confidence: 99%
“…Tipo de ocupação dos responsáveis pela família, 12 renda 3 e escolaridade dos responsáveis pela família, 12,15 têm sido relacionados aos graus de severidade de cá-rie dentária. Quanto mais desfavorável a situação socioeconômica, maior o número de dentes afetados pela cárie e maior a sua severidade.…”
Section: Discussionunclassified
“…Existe relação direta entre fatores maternos, tais como cáries ativas e consumo de açúcar, e status do índice de número de dentes decíduos cariados, perdidos e obturados (ceo-d) na criança 36 . Alguns trabalhos também associaram positivamente o tabagismo materno e prevalência de cárie em seus descendentes 37,38 . Observou-se menor índice e menor severidade de cárie nas crianças cujas mães as levavam com mais regularidade para consultas odontológicas periódicas de controle 39 .…”
Section: Etiologia E Fatores De Risco Para O Desenvolvimento Da Doençunclassified